Inovação no setor orizícola: - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Rice is an elementary cereal for the human nutrition, that supplies energy for the organism and it became one of the greatest commodities for the world economy. It is considered a food with great productivity, economic, social and nutrition potential In Brazil and Rio Grande do Sul has the highest grain production in the country. There is a need for innovation to expand the characteristics of the cereal and a differentiation in the Brazilian rice chain, given that there are sweet products based on industrialized rice in other places of the world. It is important the food has safety and quality for the costumer, as rice derivatives may present microbiological hazards and create healthy problems when they are not produced or stored correctly. The objective of this work was to map the production system in a cereal place and rice processing, as well as to elaborate and evaluate the characteristics of a dairy dessert based on rice. The first part was consisted in a study in one of the cereal place and rice processing located in Rosário do Sul city. The technical visits took place for knowledge and mapping of the processes routinely developed in the agroindustry. The second part developed a rice based dessert formulation and accompanied the microbiological stability and sensory acceptance. The dessert was formulated following the good practices and with standardized protocols. The microbiological analysis included Salmonella sp., Listeria sp., Bacillus Cereus, Staphylococcus Aureus and total coliform group. The sensory evaluation was done by untrained tasters through acceptance tests for color, odor, flavor and texture and purchase intention attributes. In the mapping of the processes of the beneficiation cereal worker, procedures were followed from the arrival of paddy rice until the final products are obtained with the elaboration of flowcharts and validation of processes that occur daily. The formulated product did not show detection of Salmonella sp., Listeria sp., Bacillus Cereus, Staphylococcus Aureus and total coliform group at 5 and 25 days of refrigerated storage, demonstrating good quality and microbial stability during this period. The evaluation of sensory attributes revealed average values between 7 and 8 that refer to “I liked it” and “I liked it so much”. In the buying intention, the notes were in the region of “possibly” or “certainly I would buy”, but some tasters pointed out that the texture should be improved. Rice has significant economic and cultural values, therefore strategies must be developed for its harnessing and diversification of derivates. The formulation of rice-based dairy dessert can be a strategy, as well as the harnessing of by-products from cereal industry, innovating in the market for one of the most consumed cereals in the world.
mapeamento de processos e oportunidades de mercado
Keywords: Arroz; Agroindústria; Estabilidade microbiológica; Rice; Agroindustry; Microbiological stability; CNPQ::CIENCIAS BIOLOGICAS